Preparation method and application of calcium zinc composite heat stabilizer

By using a preparation method of using a new type of calcium -zinc compound thermal stabilizer during the processing of polyvinyl chloride thermal formation, the problem of insufficient adaptability and high use cost in the existing technologies in the existing technology, and realizing the stability of product performance And cost control.

CN119119574BActive Publication Date: 2025-01-28SHANDONG YUEHUI NEW MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411621525.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-28
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The existing calcium-zinc composite heat stabilizers do not adapt to thermoforming processing conditions in polyvinyl chloride thermoforming processing, resulting in difficulty in forming the recipe, unstable product performance, and high usage cost.

Method used

Adopting a calcium -zinc composite thermal stabilizer preparation method, by heating orthopatane, oleic acid, and niche acid in the reactor that isolates the air, add powder -like active zinc oxide, perform a slight boiling response, and then add oil acid and powder -like Calcium carbonate slurry continues to react and spray drying to obtain calcium zinc compound armal stabilizers.

Benefits of technology

The calcium -zinc composite thermal stabilizer prepared by this method shows good adaptability in the heat molding processing of polyvinyl chloride products. Thermal forming processing ingredients are easy to formulate, the product performance is stable, and the cost of use is basically not increased.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of processing aids, and specifically relates to a preparation method and application of a calcium-zinc composite heat stabilizer. The preparation method comprises the following steps: (1) in a reactor isolated from air and equipped with a condensation reflux water separator, adding n-hexane, oleic acid and adipic acid and stirring, then adding powdered active zinc oxide, turning on the condensation reflux, heating and keeping the liquid slightly boiling, reacting until the solution is clear, and obtaining a zinc-containing solution; (2) the zinc-containing solution of step (1) is continuously stirred and kept slightly boiling, and a room temperature slurry mixed with oleic acid and powdered calcium carbonate is added to obtain a zinc-calcium solution; (3) the zinc-calcium solution of step (2) is spray-dried under anaerobic conditions to obtain a calcium-zinc composite heat stabilizer. The prepared calcium-zinc composite heat stabilizer has good adaptability in the application of the thermoforming process of polyvinyl chloride products, the ingredients are easy to formulate, the performance of the products is relatively stable, and it has certain application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of processing aids, and specifically relates to a preparation method and application of a calcium-zinc composite heat stabilizer. Background Art

[0002] Polyvinyl chloride, abbreviated as PVC, is a thermoplastic polymer obtained by free radical polymerization with vinyl chloride as the monomer. Its products have excellent mechanical properties, easily adjustable hardness and softness, good corrosion resistance and electrical insulation properties, and are widely used in chemical, building materials, automobile, electric power, electronics and agriculture.

[0003] In polyvinyl chloride resin, most of the PVC molecules have a linear and relatively stable structure. However, due to the limitations of the polymerization mechanism and the production process, the structure of some PVC molecules in polyvinyl chloride resin is not stable enough. Under temperature conditions such as around 100°C, degradation reactions begin to occur and HCl is released. The degradation reaction is more significant at 170-200°C. If the released HCl cannot be quickly discharged or converted, it will significantly accelerate the degradation reaction and even cause the degradation of PVC molecules with a linear and relatively stable structure, resulting in poor resin performance. Therefore, the thermoforming processing ingredients of polyvinyl chloride products usually contain heat stabilizers to quickly absorb the HCl released by the pyrolysis reaction; during the thermoforming process, the polyvinyl chloride resin and the mixed fillers, plasticizers, heat stabilizers and other ingredients gradually heat up, and the highest temperature generally reaches 185-205°C. Strong shearing can also cause HCl to be released.

[0004] The heat stabilizers used in the thermoforming processing of polyvinyl chloride products include lead salts, organic tin, calcium zinc and rare earth. Among them, calcium zinc heat stabilizers have a high cost performance. For example, zinc soap and calcium soap of carboxylic acids such as stearic acid, oleic acid and adipic acid are usually composited by separately prepared zinc soap and calcium soap. Rare earth soap of carboxylic acids such as stearic acid and oleic acid can also be added to play a synergistic role. Zinc soap can be added to the calcium zinc composite heat stabilizer, which can quickly absorb HCl produced by pyrolysis of PVC and generate ZnCl 2 , but ZnCl 2 As a Lewis acid, it has a catalytic effect on the thermal decomposition of zinc soap and PVC resin at processing temperatures above 170°C. The main function of calcium soap and rare earth soap is to capture the generated ZnCl 2 Cl in ZnCl 2 Regenerate into zinc soap and continue to play the role of zinc soap, the generated CaCl 2It has no catalytic effect on the pyrolysis of zinc soap and pyrolysis of PVC resin, thus ensuring the stability of PVC resin during thermal processing; the reason for using stearic acid and oleic acid is that the carbon chains of the two are relatively long, and the melting points of zinc soap, calcium soap and rare earth soap are relatively low and easy to disperse in PVC resin, and not easy to precipitate on the surface of the product. When the composition, calcium-zinc ratio, preparation method and application method of the calcium-zinc composite heat stabilizer are not appropriate, the color of the material caused by the pyrolysis of zinc soap is prone to change, such as from white to yellow, brown, brown, and in more serious cases, "zinc burning" will occur, that is, black spots will appear on the surface and cross section of the molten material or product, or even all black; one of the items for evaluating the performance of calcium-zinc heat stabilizers is the heat stability time of the calcium-zinc heat stabilizer and polyvinyl chloride resin during the process of heating and melting, or the heat stability time of the plastic test piece produced at the test temperature includes the time when "zinc burning" occurs. The calcium-zinc composite heat stabilizer may also be formulated with auxiliary heat stabilizers, antioxidants and other ingredients that match it. The auxiliary heat stabilizers include pentaerythritol, β-diketone, hydrotalcite, metal organic framework materials and the like, and the antioxidants include hindered phenol antioxidant 1010 and the like.

[0005] Chinese patent CN101575424A discloses a method for preparing a calcium-zinc composite stabilizer using chelating technology, comprising the following steps: (1) mixing four components of dibasic or polybasic saturated acid calcium, dibasic or polybasic saturated acid zinc, antioxidant, and co-stabilizer in a reaction kettle according to a mass ratio and stirring at a low speed for 2-10 minutes; wherein the dibasic or polybasic saturated acid calcium is calcium adipate, calcium glycerate, or calcium pimelate; the dibasic or polybasic saturated acid zinc is zinc pimelate, zinc adipate, or zinc glycerate; the antioxidant The oxidant is one or a mixture of 2,6-tert-butyl-4-methylphenol, bis(3,5-tert-butyl-4-hydroxyphenyl) sulfide, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (i.e. hindered phenol antioxidant 1010), (2,4-di-tert-butylphenyl) phosphite, trioctyl phosphite, tridecyl phosphite; the co-stabilizer is epoxidized soybean oil, hydrotalcite or phenyl maleimide; the mass ratio of the above four components is:

[0006] Dibasic or polybasic saturated calcium 10-30%

[0007] Zinc in dibasic or polybasic saturated acid 10-30%

[0008] Antioxidant 5-15%

[0009] Costabilizer 10-35%;

[0010] (2) When the mixture is heated to 50-80° C. in a reaction kettle, a chelating agent accounting for 3-20% by mass of the mixture is added under stirring, and the stirring speed is controlled at 2000-3000 rpm, wherein the chelating agent is one of dimerized aspartic acid green chelating agent or catechol aminocarboxylic acid chelating agent or a mixture of the two; (3) When the reaction temperature is controlled to be higher than the melting point of the lubricant to be added, a lubricant accounting for 10-20% by mass of the mixture is added to the reaction kettle, and the mixture is mixed with the calcium zinc stabilizer under stirring for 10 minutes; wherein the lubricant is one of butyl stearate, glyceryl monostearate, ester wax or saponified wax or a mixture of several thereof; (4) After cooling to room temperature, the mixture is stirred at a low speed for 1-5 minutes to obtain a calcium zinc composite stabilizer.

[0011] Chinese patent CN110951111A discloses a liquid calcium-zinc composite stabilizer, which is prepared from the following components:

[0012] 100 parts by weight of a mixture of zinc oleate and calcium oleate;

[0013] Calcium benzoate 3-10 parts by weight;

[0014] 100-250 parts by weight of dinonyl adipate;

[0015] Phosphite 30-60 parts by weight;

[0016] Solvent oil 30-60 parts by weight;

[0017] 5-30 parts by weight of β-diketone;

[0018] The mass ratio of zinc oleate to calcium oleate in the zinc oleate to calcium oleate mixture is 1:(0.2-4); the mass ratio of calcium oleate to calcium benzoate can be (5-11):1; the β-diketone is one or more selected from acetylacetone, benzoyl acetone, stearoylbenzoylmethane, dibenzoylmethane, ethyl acetoacetate, and dehydroacetic acid; the phosphite is one or more selected from diisooctylphenyl phosphite, trioctyl phosphite, triphenyl phosphite, and trinonyl phosphite.

[0019] Chinese patent CN109232975A discloses a preparation method of a liquid calcium zinc heat stabilizer for PVC, comprising the following steps: S1, adding oxidized vegetable oil as a solvent into a reactor, then adding benzoic acid and ricinoleic acid, heating to 75-85°C, adding calcium hydroxide, hydrogen peroxide and diethylene glycol monobutyl ether, and stirring and reacting for a period of time; the oxidized vegetable oil is one or more selected from oxidized peanut oil, oxidized corn oil, oxidized soybean oil, and oxidized sunflower oil; S2, adding zinc oxide and hydrogen peroxide into the reactor, and continuing to stir and react for a period of time; S3, heating to 100-110°C, performing vacuum dehydration, then cooling to 85-95°C, adding bisphenol A, pentaerythritol, β-diketone, triphenyl phosphite, dodecanol and diethylene glycol monobutyl ether, then cooling to 75-85°C and continuing to stir and react until the reaction is completed, thereby obtaining a liquid calcium zinc heat stabilizer for PVC; wherein, based on a total addition amount of 100 parts by mass:

[0020] The amount of oxidized vegetable oil added is 40 to 55 parts;

[0021] The mass ratio of the total amount of benzoic acid and ricinoleic acid added to the oxidized vegetable oil is 1:(2-5);

[0022] The mass ratio of benzoic acid to ricinoleic acid is (5-1):(1-3);

[0023] The amount of calcium hydroxide added is 2 to 5 parts;

[0024] The molar ratio of calcium hydroxide to zinc oxide is (2-5):1;

[0025] The total amount of hydrogen peroxide added twice is 1 to 2 parts;

[0026] The amount of bisphenol A added is 1 to 5 parts;

[0027] The amount of pentaerythritol added is 0.3 to 3 parts;

[0028] The amount of β-diketone added is 0.3 to 1.5 parts;

[0029] The amount of triphenyl phosphite added is 6 to 16 parts;

[0030] The amount of dodecanol added is 4 to 7 parts;

[0031] The total amount of diethylene glycol monobutyl ether added twice is 2.5 to 4.5 parts.

[0032] Chinese patent CN116178792A discloses a calcium-zinc MOFs composite thermal stabilizer, which comprises 8-10 parts of a main stabilizer and 0.5-2 parts of an auxiliary stabilizer by weight; the main stabilizer is a mixture of calcium stearate and zinc stearate; the auxiliary stabilizer is one or more of metal organic framework materials aromatic carboxylic acid organic ligand MOFs, nitrogen-containing heterocyclic and carboxyl mixed ligand MOFs, or two carboxylic acid mixed ligand MOFs, and the specific surface area of ​​MOFs can be 2200-6240m 2 / g.

[0033] The disadvantages of the above-mentioned patents CN101575424A, CN110951111A, CN109232975A or similar technologies are that in polyvinyl chloride thermoforming products, the amount of zinc soap and calcium soap used, calculated as the total amount, is generally more than 2.5wt% of the amount of polyvinyl chloride resin used, and the effect is better when the zinc-calcium molar ratio is 1:(2-3). The adaptability to thermoforming processing conditions such as equipment conditions and / or raw material ratio adjustment is not good enough, which also leads to difficulties in formulating thermoforming processing ingredients or unstable product performance; the disadvantages of patent CN116178792A or similar technologies are that the auxiliary stabilizer MOFs is difficult to prepare and the cost is very high, and the performance is not stable enough, so it is difficult to use; the hydrotalcite in patent CN101575424A or similar technologies also has the problems of high preparation cost and unstable performance. Summary of the invention

[0034] In view of the deficiencies in the prior art, the problem to be solved by the present invention is: to provide a method for preparing a calcium-zinc composite heat stabilizer, which has good adaptability to thermoforming processing conditions such as equipment conditions and / or raw material ratio adjustment during the thermoforming application of polyvinyl chloride products, and the thermoforming processing ingredients are easier to formulate, the product performance is relatively stable, and the use cost is basically not increased.

[0035] The technical solution adopted by the present invention to solve its technical problem is:

[0036] The present invention provides a method for preparing a calcium-zinc composite heat stabilizer, comprising the following steps:

[0037] (1) In a reactor isolated from air and equipped with a condensation reflux water separator, add n-hexane, oleic acid and adipic acid, stir, then add powdered active zinc oxide, start condensation reflux, increase the temperature and keep the liquid slightly boiling, react until the solution is clear, and obtain a zinc-containing solution;

[0038] (2) The zinc-containing solution of step (1) is continuously stirred and kept at a slight boil, and a room temperature slurry of oleic acid and powdered calcium carbonate is added to obtain a zinc-calcium solution;

[0039] (3) spray drying the zinc-calcium solution in step (2) under anaerobic conditions to obtain a calcium-zinc composite heat stabilizer;

[0040] In step (1), the weight ratio of n-hexane to the total amount of adipic acid and oleic acid is 1:(0.22-0.3), and the molar ratio of adipic acid, oleic acid and zinc oxide is 1:(1-1.06):(0.87-1);

[0041] In step (2), the molar ratio of calcium carbonate to oleic acid in the room temperature slurry is 1:(0.91-1), and the molar ratio of calcium carbonate to zinc oxide in step (1) is 1:(0.83-1).

[0042] in:

[0043] The specific surface area of ​​the powdered active zinc oxide in step (1) is 39-45 m 2 / g, the reaction time is 1.1-1.5h, the molar ratio of adipic acid, oleic acid, zinc oxide in step (1) to calcium carbonate in step (2) is 1:2:1:1, the equivalent average diameter of the powdered calcium carbonate in step (2) is less than 3μm, the room temperature slurry is added for 2-2.5h, and after the addition is completed, the reflux reaction is continued for 1-1.5h to obtain a zinc-calcium solution.

[0044] In steps (1) and (2), the reflux uses circulating water at 15-20°C as a cooling medium, the condensate is separated into oil and water, the upper oil phase, i.e., n-hexane, flows back to the reactor, and the bottom water phase is discharged regularly; the micro-boiling reaction temperature of the feed liquid is 72-75°C. The boiling point of the solvent n-hexane at normal pressure is 69°C.

[0045] In step (3), the spray drying uses a carbon dioxide-rich gas flow or a nitrogen-rich gas flow as a circulating heat carrier, the inlet gas flow temperature of the circulating heat carrier is 155-160°C, the outlet gas flow temperature of the circulating heat carrier is 75-80°C, and the discharge temperature of the calcium-zinc composite heat stabilizer is 85-90°C; the outlet gas flow is cooled to 10-15°C, and the condensed n-hexane is recovered, and the gas flow after the condensed n-hexane is recycled, that is, the carbon dioxide-rich gas flow or the nitrogen-rich gas flow, which is heated to 155-160°C for recycling, and the remaining components in the carbon dioxide-rich gas flow or the nitrogen-rich gas flow are n-hexane. During the spray drying process, it is best to maintain a system positive pressure of more than 5kPa to reduce the amount of air infiltration and ensure operation safety.

[0046] In step (3), calcium stearate is added to the zinc-calcium solution before spray drying and dissolved until uniform, so that the molar ratio of Ca to Zn in the obtained calcium-zinc composite heat stabilizer is (1.3-1.8):1; the calcium-zinc composite heat stabilizer can be used for some polyvinyl chloride raw materials with lower quality grades.

[0047] In step (3), β-diketone is added to the zinc-calcium solution before spray drying and dissolved until uniform, and the amount of addition is 21-30wt% of the solute components contained in the zinc-calcium solution, i.e., the components other than n-hexane in the zinc-calcium solution in step (2). The β-diketone is benzoyl acetone or stearoyl benzoyl methane.

[0048] In step (3), an antioxidant 1010, i.e., pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, is added to the zinc-calcium solution before spray drying and dissolved until uniform. The amount of the antioxidant 1010 is 21-25 wt % of the solute components contained in the zinc-calcium solution, i.e., the components other than n-hexane in the zinc-calcium solution in step (2).

[0049] In step (3), an ultraviolet absorber UV-9 or UV-531 is added to the zinc-calcium solution before spray drying and dissolved until uniform. The amount added is 20-25wt% of the solute components contained in the zinc-calcium solution, i.e., the components other than n-hexane in the zinc-calcium solution in step (2).

[0050] The calcium-zinc composite heat stabilizer prepared by the preparation method of the calcium-zinc composite heat stabilizer is used in the thermoforming processing of polyvinyl chloride products, and the weight ratio of polyvinyl chloride powder to the calcium-zinc composite heat stabilizer in the ingredients is 100:(1.5-1.8), and the maximum processing temperature is 190-200°C.

[0051] The calcium-zinc composite heat stabilizer is used in the hot forming process of polyvinyl chloride products. The polyvinyl chloride products include soft products and hard products. When preparing soft products, 40-60 parts of dioctyl phthalate are added to the ingredients; when preparing hard products, 40-60 parts of active calcium carbonate are added to the ingredients.

[0052] The calcium-zinc composite heat stabilizer prepared by the present invention has good adaptability to heat forming processing conditions such as equipment conditions and / or raw material ratio adjustment in the application of polyvinyl chloride product heat forming process, is easy to formulate heat forming processing ingredients, has relatively stable product performance, and basically does not increase the use cost. It is applicable to both the ingredients in normal production and the ingredients in the shutdown process, and the upper limit ratio can be used in the ingredients in the shutdown process, and has certain application prospects.

[0053] From the effects of the following embodiments and comparative examples, it is believed that the main principles of the present invention are as follows, and the above beneficial effects are also the result of the following factors:

[0054] 1. In step (1) of the present invention, the suspension containing powdered active zinc oxide gradually reacts and becomes clear, and the obtained zinc-containing solution is slightly acidic. After being diluted 10 times with dimethyl sulfoxide at room temperature, the pH value is about 5 as measured by an acidity meter; in step (2), during most of the time during the continuous injection of oleic acid and powdered calcium carbonate slurry, the dissolution rate of calcium carbonate is relatively fast, and the accumulated amount of calcium carbonate powder in the slurry is much lower than the added amount. The rotor flowmeter and the volume flowmeter connected in series at the upper port of the condenser reflux device show that airflow is generated. According to the flow rate and total volume change of the exhaust gas, and the phenomenon that the exhaust gas can make the calcium hydroxide aqueous solution turbid, it is indicated that carbon dioxide is generated and discharged.

[0055] Combined with the phenomena in the preparation experiments of Comparative Examples 1-3 and the test results, as well as the effect of the prepared calcium-zinc composite heat stabilizer in the application of thermoforming of polyvinyl chloride products and the difference from the effect of the relevant comparative examples, it is judged that the product after the reaction in step (1) is mainly C 17 H 33 COO-Zn-OOCC 4 H 8 COOH, the products of the reaction in step (2) are mainly C 17 H 33 COO-Zn-OOCC 4 H 8 COO-Ca-OOCC 17 H 33 The two-step reaction carried out in n-hexane solvent and slightly boiling dehydration conditions is completely different from the reaction carried out in aqueous solution conditions, and is also difficult to achieve under aqueous solution conditions. It is unexpected that the organic acids adipic acid and oleic acid can react with zinc oxide and calcium carbonate in the inert solvent n-hexane.

[0056] For example, in comparative example 1, under reaction conditions similar to those in step (1), after sufficient reaction of adipic acid and zinc oxide in molar ratios of 1:1 and 1:0.5, respectively, no clear solution can be obtained. The solution in the molar ratio of 1:0.5 is acidic after reaction, and the pH value is about 5 after dilution with dimethyl sulfoxide at room temperature by an acidometer. The solution in the molar ratio of 1:1 is not acidic after reaction, and the pH value is above 6.5 after dilution with dimethyl sulfoxide at room temperature by an acidometer. This indicates that under these two reaction conditions, the zinc salt of adipic acid generated cannot be completely dissolved and precipitated.

[0057] Comparative Example 2: No bubbles were generated during the process of leaving the slurry in step (2) at room temperature for 6 hours. The molar ratio of oleic acid to calcium carbonate was 1:1. No bubbles were generated during the process of treating the slurry at 65° C. with double the volume of n-hexane at a constant temperature of 65° C. for 3 hours. The slurry was treated under slightly boiling and reflux water separation conditions for 2 hours. During the treatment, the rotor flowmeter and the volume flowmeter connected in series to the gas outlet of the reflux water separator showed no gas discharge, indicating that oleic acid and calcium carbonate basically did not react to discharge carbon dioxide under these conditions.

[0058] 2. The main reason why the calcium-zinc composite heat stabilizer prepared by the present invention has a good effect in the application process of thermoforming of polyvinyl chloride products is that the zinc and calcium components are combined in C 17 H 33 COO-Zn-OOCC 4 H 8 COO-Ca-OOCC 17 H 33 Its molecular weight is 787, its zinc content is 8.3wt%, its calcium content is 5.0wt%, and its molecular structure has long-chain hydrocarbon groups of oleic acid at both ends, which has good lipophilicity and is easy to disperse evenly in the polyvinyl chloride melt. The calcium and zinc content is high and there is only one adipic acid group between calcium and zinc in the molecule. The HCl captured by zinc is easier to transfer to calcium quickly.

[0059] The main reason why the calcium-zinc composite heat stabilizer prepared in Comparative Example 4 or Comparative Example 5 cannot achieve the application effect of the calcium-zinc composite heat stabilizer prepared in the present invention is that the calcium oleate and zinc-rich soap substances such as C 17 H 33 COO-Zn-OOCC 4 H 8 COO-Ca-OOCC 4 H 8 COO-Zn-OOCC 17 H 33 Or calcium adipate and zinc-rich soaps such as C 17 H 33 COO-Zn-OOCC 4 H 8 COO-Ca-OOCC 4 H 8 COO-Zn-OOCC 17 H 33 , C 17 H 33 COO-Zn-OOCC 4 H 8 COO-Zn-OOCC 4 H 8 COO-Zn-OOCC 17 H 33The transfer rate of HCl captured by zinc to calcium is slow; the calcium-zinc composite heat stabilizer in the prior art usually also has this problem. The dosage calculated by the total amount of zinc soap and calcium soap is large, generally more than 3wt% of the amount of polyvinyl chloride resin, and the heat stabilization effect is better when the zinc-calcium molar ratio is 1: (2.5-3). DETAILED DESCRIPTION

[0060] The technical solution of the present invention is specifically described and illustrated below in conjunction with embodiments.

[0061] Example 1

[0062] The calcium-zinc composite heat stabilizer of this embodiment is prepared by the following steps:

[0063] (1) A clean, dry 1000 mL three-necked glass flask was fixed on an iron stand and an electromagnetic stirring heater. A cylindrical glass tube was installed outside the flask to assist in heat preservation. A glass condensation reflux water separator and a thermometer were installed. 99.9% nitrogen was introduced into the bottom of the flask to remove air for 5 minutes. 300 g of n-hexane, 42.66 g of oleic acid, and 21.92 g of adipic acid were added based on the pure product. A stirring bar was added. The condensation reflux and stirring were started. 12.21 g of powdered active zinc oxide was added based on the pure product. The heating was started until the liquid was slightly boiled and maintained. The reaction was continued for 1.1 hours until the solution was clear to obtain a zinc-containing solution. The specific surface area of ​​the added powdered active zinc oxide was 39 m 2 / g, an average particle size of 42 μm, a weight ratio of n-hexane to the total amount of adipic acid and oleic acid of 1:0.22, and a molar ratio of adipic acid, oleic acid, and zinc oxide of 1:1:1;

[0064] (2) The zinc-containing solution of step (1) is continuously stirred and kept at a slight boil, and a room temperature slurry of oleic acid and powdered calcium carbonate is added. On a pure basis, 42.66 g of oleic acid and 15.00 g of heavy calcium carbonate with an average particle size of 2.2 μm are stirred to obtain a slurry. The molar ratio of calcium carbonate to oleic acid is 1:1. The room temperature slurry is added for 2 hours, and about 2.4 g is added every 5 minutes. The reflux reaction is continued for 1 hour to obtain a zinc-calcium solution.

[0065] (3) The zinc-calcium solution of step (2) was spray-dried under anaerobic conditions, and the average particle size of the powder was controlled to be 20-30 μm, to obtain 115 g of calcium-zinc composite thermal stabilizer;

[0066] In steps (1) and (2), the reflux water separator uses circulating water at 15-20°C as the cooling medium. The condensate is separated into oil and water, and the upper oil phase, i.e., n-hexane, flows back to the reactor, and the bottom water phase is discharged regularly.

[0067] In step (3), during the spray drying process, a nitrogen-rich gas flow is used as a circulating heat carrier, and the inlet and outlet gas flow temperatures are controlled to be 155-160°C and 75-80°C, respectively. The discharge temperature of the dried powder, i.e., the inlet temperature, is controlled to be 85-90°C. The outlet gas flow is first cooled to 10-15°C, and the gas flow after separation and recovery of the n-hexane condensate is the nitrogen-rich gas flow, and the components other than nitrogen are n-hexane, which is heated to 155-160°C for recycling. A proper amount of nitrogen is added to the 10-15°C gas flow after separation of the n-hexane condensate to maintain a system positive pressure of 5-10 kPa, so as to reduce the amount of air infiltration and ensure operation safety. The purity of the raw nitrogen is 99.9%.

[0068] In the total ingredients of steps (1) and (2), the molar ratio of adipic acid, oleic acid, zinc oxide and calcium carbonate is 1:2:1:1; during the micro-boiling reaction of the two liquids, the liquid temperature can be controlled within the range of 72-75°C; and the purity of each raw material used exceeds 99wt%.

[0069] The calcium-zinc solution obtained in step (2) is sampled and tested; the operation of step (1) is repeated once, and the zinc solution obtained is sampled and tested.

[0070] The main effects of the operation of Example 1 include: in step (1), the suspension containing powdered active zinc oxide gradually reacts and becomes clear, and the obtained zinc-containing solution is slightly acidic. After being diluted 10 times with dimethyl sulfoxide at room temperature, the pH value is about 5 as measured by an acidity meter; in step (2), during most of the time during the addition of oleic acid and powdered calcium carbonate slurry, the dissolution rate of calcium carbonate is relatively fast, and the accumulated amount of calcium carbonate powder in the slurry is much lower than the added amount. The rotor flowmeter and the volume flowmeter connected in series to the upper port of the condensation reflux water separator show that airflow is generated. According to the flow rate and total volume changes of the exhaust gas, and the phenomenon that the exhaust gas can make the calcium hydroxide aqueous solution turbid, it is indicated that carbon dioxide is generated and discharged.

[0071] Example 2

[0072] The operations of steps (1) to (3) of Example 1 were repeated, except that the feed amounts in step (1) were changed to 222 g of n-hexane, 44.79 g of oleic acid, and 21.92 g of adipic acid based on the pure product, a stirring bar was added, reflux and stirring were started, 10.72 g of powdered active zinc oxide based on the pure product was added, heating was started, and the feed liquid was kept slightly boiling, and the reaction was continued for 1.5 h until the solution was clarified to obtain a zinc-containing solution; the specific surface area of ​​the added powdered active zinc oxide was 45 m 2 / g, average particle size of 43μm, the weight ratio of the total amount of n-hexane, adipic acid and oleic acid added is 1:0.3, and the molar ratio of adipic acid, oleic acid and zinc oxide is 1:1.06:0.87; the feeding amount in step (2) is changed to oleic acid 40.53g and heavy calcium carbonate 15.75g with an average particle size of 3μm based on the pure product. In the total ingredients of steps (1) and (2), the molar ratio of adipic acid, oleic acid, zinc oxide and calcium carbonate is 1:2:0.87:1.05; the room temperature slurry is added for 2.5h, and the reflux reaction is continued for 1.5h.

[0073] The calcium-zinc solution obtained in step (2) is sampled and tested; the operation of step (1) is repeated once, and the zinc solution obtained is sampled and tested.

[0074] The main effects of the operation of this embodiment 2 are basically the same as those of the embodiment 1.

[0075] Comparative Example 1

[0076] The operation of step (1) of Example 1 was repeated once, except that no oily acid was added and the molar ratio of adipic acid to zinc oxide was kept constant at 1:1. As a result, the feed liquid was in a thin slurry state during the reaction for 3 hours. After a sample was taken and diluted 10 times with dimethyl sulfoxide at room temperature, the pH value was measured by an acidity meter to be 7.1, i.e., the feed liquid was not acidic, and it was considered that zinc adipic acid was generated, which was insoluble in n-hexane.

[0077] The operation of step (1) of Example 1 was repeated once, except that no oily acid was added, and 6.1 g of powdered active zinc oxide was added based on the pure product, that is, the molar ratio of adipic acid to zinc oxide was 1:0.5; as a result, the feed liquid was in a thin slurry state during the reaction for 3 hours. After a sample was taken and diluted 10 times with dimethyl sulfoxide at room temperature, the pH value was 5.2 as measured by an acidity meter, indicating that zinc adipate and zinc diadipate that were insoluble in n-hexane were generated, that is, only half of the terminal carboxylic acid participated in the reaction.

[0078] Comparative Example 2

[0079] A slurry prepared from 42.66 g of oleic acid and 15.00 g of heavy calcium carbonate with an average particle size of 2.2 μm used in step (2) of Example 1, with a molar ratio of oleic acid to calcium carbonate of 1:1, was placed at room temperature for 6 hours, and no bubbles were found during the placement; then, one volume of n-hexane was added and the mixture was placed at a constant temperature of 65°C for 3 hours, and no bubbles were found during the placement; the mixture was further treated under the conditions of slight boiling and condensation reflux water separation for 2 hours, and during the treatment, the rotor flowmeter and the volume flowmeter connected in series to the gas outlet of the condensation reflux water separator showed no gas flow discharge. This indicates that under these conditions, oleic acid and calcium carbonate basically did not produce a reaction to discharge carbon dioxide.

[0080] Comparative Example 3

[0081] The operations of steps (1) to (3) of Example 1 were repeated, except that the room temperature slurry of oleic acid and powdered calcium carbonate described in step (2) was prepared by mixing 42.66 g of oleic acid and 15.00 g of heavy calcium carbonate having an average particle size of 2.2 μm, and was added all at once to the slightly boiling zinc-containing solution within 2 minutes. As a result, the reaction was relatively violent, and the feed liquid was easily expanded and rose to the condensation reflux water separator due to the effect of reaction gas release and condensed a small amount on the condensation surface. The rotor flowmeter and the volume flowmeter connected in series to the gas outlet on the condensation reflux water separator both showed that gas production was relatively fast within 20 minutes after the slurry was added, making process control difficult.

[0082] Comparative Example 4

[0083] The operations of steps (1) to (3) of Example 1 were repeated to prepare 113 g of the calcium-zinc composite heat stabilizer of this comparative example, except that the room temperature slurry of oleic acid and powdered calcium carbonate described in step (2) was prepared by mixing 42.66 g of oleic acid and 15.00 g of heavy calcium carbonate with an average particle size of 2.2 μm, and the addition time to the slightly boiling zinc-containing solution was 1 h, with about 3 g added every 3 min. As a result, the reaction was relatively smooth, the feed liquid did not rise significantly to affect the operation of the condensation reflux water separator, and the process was normal and easy to control.

[0084] Comparative Example 5

[0085] Using the preparation conditions and raw materials of Example 1, the calcium-zinc composite heat stabilizer of this comparative example was prepared according to the following steps:

[0086] (a) Fix a clean, dry 1000mL three-necked glass flask on an iron stand and an electromagnetic stirring heater, install a cylindrical glass tube on the outside of the flask to assist in heat preservation, install a condensation reflux water separator and a thermometer; introduce 99.9% nitrogen into the bottom of the flask to remove air for 5 minutes, add 300g of n-hexane, 85.32g of oleic acid, and 21.92g of adipic acid based on the pure product, add a stirrer, start condensation reflux and stirring, add 12.21g of powdered active zinc oxide and 15.00g of heavy calcium carbonate based on the pure product, Turn on the heating, control the heating power to make the feed liquid react smoothly, the feed liquid rises to a small height, and the condensation reflux water separator operates normally. After heating for 53 minutes, the feed liquid is heated to 65°C, and the temperature is controlled at 65-68°C for 30 minutes, and then the feed liquid is controlled to react in a slightly boiling state for 1.5 hours until the solution is clarified to obtain a calcium-zinc solution; the weight ratio of the added n-hexane to the total amount of adipic acid and oleic acid is 1:0.36, and the molar ratio of adipic acid, oleic acid, zinc oxide and calcium carbonate is 1:2:1:1; during the slightly boiling reaction, the feed liquid temperature is 72-75°C;

[0087] (b) spray drying the zinc-calcium solution of step (a) under anaerobic conditions, and controlling the average particle size of the powder to 20-30 μm to obtain 112 g of calcium-zinc composite thermal stabilizer;

[0088] In step (a), the condensation reflux water separator uses 15-20°C circulating water as the cooling medium, the condensate is separated into oil and water, the upper oil phase, i.e., n-hexane, flows back to the reactor, and the bottom water phase is discharged regularly. In step (b), the spray drying conditions are the same as those in Example 1.

[0089] The calcium-zinc composite heat stabilizer prepared in Comparative Example 5 has an opaque molten liquid after sampling and heating; while the calcium-zinc composite heat stabilizer prepared in Example 1 can obtain a nearly transparent molten liquid after sampling and heating.

[0090] Example 3

[0091] The operations of steps (1) to (3) of Example 1 were repeated to prepare the calcium-zinc composite heat stabilizer of this example, except that, in step (3), 46.45 g of a commercial heat stabilizer calcium stearate with a purity of 98 wt % was added to the zinc-calcium solution before spray drying and dissolved until uniform, so that the molar ratio of Ca to Zn in the obtained calcium-zinc composite heat stabilizer was 1.5:1.

[0092] Example 4

[0093] The operations of steps (1) to (3) of Example 1 were repeated to prepare the calcium-zinc composite heat stabilizer of this example, except that, in step (3), 25 g of 98 wt% purity auxiliary heat stabilizer benzoyl acetone and 25 g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate were added to the zinc-calcium solution before spray drying and dissolved until uniform, and the added amounts of both were 21 wt% of the solute components contained in the zinc-calcium solution, i.e., 118 g of the components other than n-hexane in the zinc-calcium solution in step (2).

[0094] Example 5

[0095] The operations of steps (1) to (3) of Example 1 were repeated to prepare the calcium-zinc composite heat stabilizer of this example, except that, in step (3), 27.29 g of a commercial heat stabilizer calcium stearate with a purity of 98 wt % was added to the zinc-calcium solution before spray drying and dissolved until uniform, so that the molar ratio of Ca to Zn in the obtained calcium-zinc composite heat stabilizer was 1.3:1.

[0096] Example 6

[0097] The operations of steps (1) to (3) of Example 1 were repeated to prepare the calcium-zinc composite heat stabilizer of this example, except that, in step (3), 72.78 g of a commercial heat stabilizer calcium stearate with a purity of 98 wt % was added to the zinc-calcium solution before spray drying and dissolved until uniform, so that the molar ratio of Ca to Zn in the obtained calcium-zinc composite heat stabilizer was 1.8:1.

[0098] Example 7

[0099] The operations of steps (1) to (3) of Example 1 were repeated to prepare the calcium-zinc composite heat stabilizer of this example, except that, in step (3), 34.8 g of 98 wt% pure auxiliary heat stabilizer benzoyl acetone was added to the zinc-calcium solution before spray drying and dissolved until uniform, and the added amount was 30 wt% of the solute components contained in the zinc-calcium solution, i.e., 116 g of the components other than n-hexane in the zinc-calcium solution in step (2).

[0100] Example 8

[0101] The operations of steps (1) to (3) of Example 1 were repeated to prepare the calcium-zinc composite heat stabilizer of this example, except that 29.5 g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was added to the zinc-calcium solution before spray drying in step (3) and dissolved until uniform, and the added amount was 25 wt % of the solute component contained in the zinc-calcium solution, i.e., 118 g of the component other than n-hexane in the zinc-calcium solution in step (2).

[0102] Example 9

[0103] The operations of steps (1) to (3) of Example 1 were repeated to prepare the calcium-zinc composite heat stabilizer of this example, except that, in step (3), 29.5 g of ultraviolet absorber UV-9 was further added to the zinc-calcium solution before spray drying and dissolved until uniform, and the added amount was 25 wt % of the solute component contained in the zinc-calcium solution, i.e., 118 g of the component other than n-hexane in the zinc-calcium solution in step (2).

[0104] Example 10

[0105] The operations of steps (1) to (3) of Example 1 were repeated to prepare the calcium-zinc composite heat stabilizer of this example, except that, in step (3), 23 g of ultraviolet absorber UV-531 was further added to the zinc-calcium solution before spray drying and dissolved until uniform, and the added amount was 20 wt % of the solute component contained in the zinc-calcium solution, i.e., 115 g of the component other than n-hexane in the zinc-calcium solution in step (2).

[0106] Performance testing and data analysis:

[0107] 1. The calcium-zinc composite heat stabilizers prepared in Examples 1-10 and Comparative Examples 4-5 were subjected to application experiments and tests respectively:

[0108] (I) A transparent soft film with a thickness of about 135 μm was prepared using S-700 powdered polyvinyl chloride resin produced by Qilu Petrochemical. The weight ratio of PVC, calcium-zinc composite heat stabilizer (calculated by the total amount of calcium-zinc soap) and dioctyl phthalate was 100:1.5:50. The same thermal processing conditions were controlled, and the maximum processing temperature was 190°C.

[0109] (ii) A hard sheet with a thickness of about 300 μm was prepared using S-1000 powdered polyvinyl chloride resin produced by Qilu Petrochemical. The weight ratio of PVC, calcium-zinc composite heat stabilizer (calculated by the total amount of calcium-zinc soap) and activated calcium carbonate was 100:1.8:50. The same thermal processing conditions were controlled, and the maximum processing temperature was 190°C.

[0110] The prepared transparent soft film was subjected to a static thermal stability performance test according to the GB / T9349-2002 oven method, with a temperature condition of 180°C, and the time when the color reached the reddish brown standard color card was taken as the static thermal stability time; the results included: the transparent soft films prepared using the calcium zinc composite thermal stabilizers of Examples 1-10 had a static thermal stability time of more than 80 minutes; the transparent soft films prepared using the calcium zinc composite thermal stabilizers of Comparative Examples 4-5 had a static thermal stability time of less than 65 minutes.

[0111] The prepared hard sheets were tested for static thermal stability according to the Congo red method of GB / T2917-2002, at a temperature of 180°C, with the time for the test paper to turn blue being the static thermal stability time. The results included: the hard sheets prepared using the calcium-zinc composite thermal stabilizers of Examples 1-10 had static thermal stability times exceeding 73 minutes; the hard sheets prepared using the calcium-zinc composite thermal stabilizers of Comparative Examples 4-5 had static thermal stability times at 180°C of less than 56 minutes.

[0112] The test results also include: compared with the application effect of the calcium-zinc composite heat stabilizer prepared in Example 1, the effect of the calcium-zinc composite heat stabilizer in Comparative Example 4 is slightly worse, and the effect of the calcium-zinc composite heat stabilizer in Comparative Example 5 is even worse.

[0113] Analysis shows that the product after the reaction in step (1) of Example 1-2 is basically C 17 H 33 COO-Zn-OOCC 4 H 8 COOH, the products of the reaction in step (2) are basically C 17 H 33 COO-Zn-OOCC 4 H 8 COO-Ca-OOCC 17 H 33 ; In the preparation process of the calcium-zinc composite heat stabilizer in Comparative Example 4, there may be a certain amount of calcium oleate and zinc-rich soaps such as C17 H 33 COO-Zn-OOCC 4 H 8 COO-Ca-OOCC 4 H 8 COO-Zn-OOCC 17 H 33 Comparative Example 5 During the preparation of the calcium-zinc composite heat stabilizer, there may be a large amount of calcium adipate and zinc-rich soaps such as C 17 H 33 COO-Zn-OOCC 4 H 8 COO-Ca-OOCC 4 H 8 COO-Zn-OOCC 17 H 33 , C 17 H 33 COO-Zn-OOCC 4 H 8 COO-Zn-OOCC 4 H 8 COO-Zn-OOCC 17 H 33 generate.

[0114] Overall, the calcium-zinc composite heat stabilizer prepared by the method of Example 4 has the best effect.

[0115] 2. Application of calcium zinc composite heat stabilizer in thermoforming of polyvinyl chloride products:

[0116] According to the method of Example 4, 508 kg of calcium-zinc composite heat stabilizer was prepared in a production device, and production tests of PVC pipes and PVC special-shaped parts were carried out under different equipment and raw material ratio conditions; in the ingredients, the weight ratio of PVC to calcium-zinc composite heat stabilizer was 100:(1.5-1.8), and the maximum processing temperature was 200°C.

[0117] The results of the production test include: the ingredients for thermoforming processing are easier to formulate, the product performance is relatively stable, and the use cost is basically not increased; the calcium-zinc composite heat stabilizer has good adaptability to thermoforming processing conditions such as equipment conditions and / or raw material ratio adjustment, and the product quality does not decrease after the screw machine is temporarily shut down for less than 40 minutes and then resumed operation; the produced PVC pipes and PVC special-shaped parts all meet the quality requirements.

[0118] Therefore, the method of the present invention has good application prospects.

Claims

1. A method for preparing a calcium-zinc composite heat stabilizer, characterized in that: The following steps are involved: (1) In a reactor isolated from air and equipped with a condensation reflux water separator, add n-hexane, oleic acid and adipic acid, stir, then add powdered active zinc oxide, start condensation reflux, increase the temperature and keep the liquid slightly boiling, react until the solution is clear, and obtain a zinc-containing solution; (2) The zinc-containing solution of step (1) is continuously stirred and kept at a slight boil, and a room temperature slurry of oleic acid and powdered calcium carbonate is added. The room temperature slurry is added for 2-2.5 hours. After the addition is completed, the reflux reaction is continued for 1-1.5 hours to obtain a zinc-calcium solution; (3) spray drying the zinc-calcium solution in step (2) under anaerobic conditions to obtain a calcium-zinc composite heat stabilizer; In step (1), the weight ratio of n-hexane to the total amount of adipic acid and oleic acid is 1:(0.22-0.3), and the molar ratio of adipic acid, oleic acid and zinc oxide is 1:(1-1.06):(0.87-1); In step (2), the molar ratio of calcium carbonate to oleic acid in the room temperature slurry is 1:(0.91-1), and the molar ratio of calcium carbonate to zinc oxide in step (1) is 1:(0.83-1).

2. The method for preparing a calcium-zinc composite heat stabilizer according to claim 1, characterized in that: The specific surface area of ​​the powdered active zinc oxide in step (1) is 39-45 m 2 / g, the reaction time is 1.1-1.5h, and the equivalent average diameter of the powdered calcium carbonate in step (2) is less than 3μm.

3. The method for preparing a calcium-zinc composite heat stabilizer according to claim 2, characterized in that: In steps (1) and (2), the reflux uses circulating water at 15-20°C as a cooling medium, the condensate is separated into oil and water, the upper oil phase flows back to the reactor, and the bottom water phase is discharged regularly; The slightly boiling temperature of the feed liquid is 72-75°C.

4. The method for preparing a calcium-zinc composite heat stabilizer according to claim 1, characterized in that: The spray drying in step (3) uses a carbon dioxide-rich gas flow or a nitrogen-rich gas flow as a circulating heat carrier, the inlet gas flow temperature of the circulating heat carrier is 155-160°C, the outlet gas flow temperature of the circulating heat carrier is 75-80°C, and the discharge temperature of the calcium-zinc composite heat stabilizer is 85-90°C; the outlet gas flow is cooled to 10-15°C, and the condensed n-hexane is recovered, and the gas flow after the condensed n-hexane is recovered is recycled.

5. The method for preparing the calcium-zinc composite heat stabilizer according to claim 1, characterized in that: In step (3), calcium stearate is added to the zinc-calcium solution before spray drying and dissolved until uniform, so that the molar ratio of Ca to Zn in the obtained calcium-zinc composite heat stabilizer is (1.3-1.8):

1.

6. The method for preparing the calcium-zinc composite heat stabilizer according to claim 1, characterized in that: In step (3), an auxiliary heat stabilizer β-diketone is added to the zinc-calcium solution before spray drying and dissolved until uniform, and the added amount is 21-30wt% of the solute components contained in the zinc-calcium solution.

7. The method for preparing the calcium-zinc composite heat stabilizer according to claim 1, characterized in that: In step (3), antioxidant 1010 is added to the zinc-calcium solution before spray drying and dissolved until uniform, and the added amount is 21-25wt% of the solute components contained in the zinc-calcium solution.

8. The method for preparing a calcium-zinc composite heat stabilizer according to claim 1, characterized in that: In step (3), ultraviolet absorber UV-9 or UV-531 is added to the zinc-calcium solution before spray drying and dissolved until uniform, and the added amount is 20-25wt% of the solute components contained in the zinc-calcium solution.

9. Use of a calcium-zinc composite heat stabilizer prepared by the preparation method of a calcium-zinc composite heat stabilizer according to any one of claims 1 to 8 in thermoforming processing of polyvinyl chloride products, characterized in that: The weight ratio of polyvinyl chloride powder to calcium zinc composite heat stabilizer in the ingredients is 100:(1.5-1.8), and the maximum processing temperature is 190-200°C.

10. The use of the calcium-zinc composite heat stabilizer in the thermoforming process of polyvinyl chloride products as claimed in claim 9, characterized in that: Polyvinyl chloride products include soft products and hard products. Dioctyl phthalate is added to the ingredients when preparing soft products; activated calcium carbonate is added to the ingredients when preparing hard products.

Citation Information

Patent Citations

  • Method for preparing calcium-zinc composite stabilizing agent by adopting chelating technology

    CN101575424A

  • Liquid calcium-zinc heat stabilizer for PVC (polyvinyl chloride) and preparation method of liquid calcium-zinc heat stabilizer

    CN109232975A

  • Calcium-zinc MOFs composite heat stabilizer as well as preparation method and application thereof

    CN116178792A

  • Preparation method of high-transparent high heat resistance liquid calcium-zinc heat stabilizer

    CN102086271A

  • Liquid calcium-zinc composite stabilizer

    CN110951111A